Nutritional and cognitive health assessment among elderly at geriatric care facilities, Hyderabad: a cross sectional study - Begum, Nasreen; Pranathi, Bandi S. L. (International Journal Of Community Medicine And Public Health, 2025)
Background: With the global rise in the elderly population, ensuring their health and well-being has become critical. Nutrition plays a vital role in maintaining cognitive function, while cognitive health influences dietary habits. This study assessed nutritional status and cognitive function among elderly residents in geriatric care facilities. Methods: A cross-sectional study was conducted from July 2024 to September 2024 at two geriatric care facilities in Hyderabad (Srimatha Old Age Home, Kukatpally and HCAH Old Age Home, Gachibowli). Sixty-seven elderly residents were assessed using the mini nutritional assessment (MNA) for nutritional status and mini-mental state examination (MMSE) for cognitive function. Anthropometric measurements were recorded. Results: Among participants (47.8% male, 52.2% female), MNA revealed 46.3% had normal nutrition, 46.3% were at risk of malnutrition, and 7.4% were malnourished. MMSE scores showed 17.9% had no cognitive impairment, 34.3% had mild decline, and 47.8% had severe impairment. Conclusions: Malnutrition risk and cognitive impairment are prevalent among elderly in care facilities. Regular assessments and holistic interventions addressing nutrition, cognitive stimulation, and social engagement are essential to improve their quality of life.